2015
DOI: 10.1016/j.tust.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behaviour of a sprayed concrete lining isolated by a sprayed waterproofing membrane

Abstract: A waterproofing membrane has an important role in a sprayed concrete lined (SCL) tunnel. In this study, the mechanical behaviour of an SCL with a sprayed waterproofing membrane was investigated by laboratory testing. Two different types of tests were performed to examine the behaviour at different parts of an SCL tunnel linings around a tunnel junction. A four-point bending test was conducted to investigate the behaviour of tunnel linings under a large bending moment, which would represent a section near the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…Recent reported testing of membranes for waterproof SCL (Su et al 2013;Su and Bloodworth 2014;Nakashima et al 2015) have not included the moisture condition and moisture properties of the constituent materials in the lining. Testing of moisture properties of membrane and concrete materials have yet to be included in guidance for design and testing of spray applied membranes.…”
Section: Moisture Properties Of Lining Materialsmentioning
confidence: 99%
“…Recent reported testing of membranes for waterproof SCL (Su et al 2013;Su and Bloodworth 2014;Nakashima et al 2015) have not included the moisture condition and moisture properties of the constituent materials in the lining. Testing of moisture properties of membrane and concrete materials have yet to be included in guidance for design and testing of spray applied membranes.…”
Section: Moisture Properties Of Lining Materialsmentioning
confidence: 99%
“…On the one hand, the polymer film can help meet the impermeability demand of the lining structure; on the other hand, this film exhibits sufficient load-bearing capacity and thus can serve as a shear connection layer. Nakashima et al (2015) conducted compression-bending tests on concrete members containing 3 mm thick EVA polymer-based waterproofing membranes. The results showed that concrete members containing waterproofing membranes behaved in a compound manner, indicating that waterproofing membranes can transfer interfacial normal and tangential interactions.…”
Section: Ec 416 1640mentioning
confidence: 99%
“…Values of interface compression and tension stiffness and strength were not proposed. Nakashima et al [57] presented flexural tests on two composite SCL beams (with sandwiched EVA based sprayed membrane) with and without axial force under ambient laboratory conditions. No information is given on mechanical properties of the membrane interface.…”
Section: Wet Dry Partially Saturated)mentioning
confidence: 99%